2015
DOI: 10.1074/jbc.m115.640920
|View full text |Cite
|
Sign up to set email alerts
|

Sec22 Regulates Endoplasmic Reticulum Morphology but Not Autophagy and Is Required for Eye Development in Drosophila

Abstract: Background: ER morphological changes are often observed in disease conditions, but the molecular mechanisms remain unclear. Results: Malfunction of Sec22 and its binding partners resulted in ER expansion and defects in fly eye development. Conclusion: Sec22 regulates ER morphology through regulating ER-Golgi trafficking but not autophagy. Significance: ER morphology changes under the disease conditions might be due to the defects of ER-Golgi trafficking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 47 publications
(52 reference statements)
6
36
0
Order By: Relevance
“…Consistent with the previous report, the majority of Syx5 EP2313 mutant photoreceptors displayed larger numbers of ER membranes compared to that in the wild-type (Zhao et al, 2015). However, we found more notable abnormalities in Golgi units than ER.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the previous report, the majority of Syx5 EP2313 mutant photoreceptors displayed larger numbers of ER membranes compared to that in the wild-type (Zhao et al, 2015). However, we found more notable abnormalities in Golgi units than ER.…”
Section: Resultssupporting
confidence: 92%
“…In a previous study, ectopic expression of ER-resident KDEL receptor in Syx5-deficient fat body cells displayed abnormal localization, suggesting ER membrane malformation (Zhao et al, 2015). Thus, we next determined the localization, and the level of resident proteins in ER and Golgi.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…S3). In a recent study, enlarged late endosomes were observed in D. melanogaster Sec22 mutants and were suggested to result from defective ER-Golgi transport (Zhao et al 2015). Although more experiments are required to fully rule out a similar explanation for our observations, the mCherry:: SEC-22 colocalization with late endosomes indicates that, at least in C. elegans, SEC-22 affects late endosome size in a more direct manner.…”
Section: Loss Of Sec-22 Results In Enlarged Late Endosomesmentioning
confidence: 45%